How comorbidities affect the surgical treatment planning in elderly patients with head and neck cancer? - Dziemiańczyk-Pakieła, Dorota; Tołoczko-Iwaniuk, Natalia; Malinowska-Zaprzałka, Małgorzata; Nowaszewska, Beata Klaudia; Chwiedosik, Marek; Borys, Jan; Wawrzyn, Katarzyna; Sierko, Ewa (Journal of Education, Health and Sport, 2018)
BACKGROUND. Head and neck cancer is the sixth leading cancer by incidence worldwide. Surgery and postoperative radiotherapy are the current standards in the treatment of head and neck cancer (HNC). Chemotherapy in combination with the listed methods is also used. However, the choice of a treatment sequence may be different for individual patients. Can-cer patients are predominantly individuals aged 65 years and over, with a number of treat-ed or untreated concomitant diseases. Therefore, comorbidities play a very significant role in treatment planning in this group of patients. METHODS. The issue was explored in a retrospective study of medical records of 108 HNC patients hospitalized at the Department of Maxillofacial and Plastic Surgery, Medical Uni-versity of Bialystok. The study focused on patients older than 65 years old as they are most predisposed to co-existing diseases which can affect treatment planning. The data were analyzed by gender, age and presence of comorbidities as well as by lesion location, histo-pathology, cancer staging notation system (TNM), treatment methods. RESULTS. Out of all cancer patients older than 65 years old, 44 were female and 64 were male at the average age of 75 and 78 years, respectively. The oldest patients were 88 years old (female) and 90 years old (male). Comorbidities were found in 62% of cases – 66% of women and 59.4% of men. The most frequent comorbidities were: hypertension – 41%, alco-hol abuse – 17%, diabetes mellitus – 14%, hyperlipidemia – 9%, coronary heart disease – 6%, asthma – 4%, atrial fibrillation – 3% of patients. 97% of patients underwent surgery, but in 17 cases (16%) the treatment plan had to be altered due to the patients' general health. Only 3% of patients were disqualified from surgical treatment due to their general condition.CONCLUSIONS: The choice of a treatment method in HNC patients should always be individ-ualized. Comorbidities, in a severe, unregulated form may reduce treatment options or be a contraindication to standard therapy methods. Fortunately, in the majority of cases, the di-versity of available surgical treatment modalities enables the selection of the most appro-priate method for a particular patient on the basis of his/her general condition.